Insulin growth factor 1 receptor expression is associated with NOTCH1 mutation, trisomy 12 and aggressive clinical course in chronic lymphocytic leukaemia. - Francesco Maura; Laura Mosca; Sonia Fabris; Giovanna Cutrona; Serena Matis; Marta Lionetti; Luca Agnelli; Marzia Barbieri; Marianna D'Anca; Martina Manzoni; Monica Colombo; Carlotta Massucco; et al. (PLoS ONE, 2015)
IGF1R is emerging as an important gene in the pathogenesis of many solid and haematological cancers and its over-expression has been reported as frequently associated with aggressive disease and chemotherapy resistance. In this study we performed an investigation of the role of IGF1R expression in a large and representative prospective series of 217 chronic lymphocytic leukaemia (CLL) patients enrolled in the multicentre O-CLL1 protocol (clinicaltrial.gov #NCT00917540). High IGF1R gene expression was significantly associated with IGHV unmutated (IGHV-UM) status (p<0.0001), high CD38 expression (p<0.0001), trisomy 12 (p<0.0001), and del(11)(q23) (p=0.014). Interestingly, higher IGF1R expression (p=0.002) characterized patients with NOTCH1 mutation (c.7541_7542delCT), identified in 15.5% of cases of our series by next generation sequencing and ARMS-PCR. Furthermore, IGF1R expression has been proven as an independent prognostic factor associated with time to first treatment in our CLL prospective cohort. These data suggest that IGF1R may play an important role in CLL biology, in particular in aggressive CLL clones characterized by IGHV-UM, trisomy 12 and NOTCH1 mutation.